Drawing is Not Enough. Design Tools for the Reuse of Modernist Buildings - Christian Gaenshirt (Joelho)
This paper[i] re-discusses the question of design tools, a metaphor that lately has been used for different things such as simple objects, media, cultural techniques, computer programs, formal principles or thinking strategies. After reviewing recent research on design tools, a taxonomy will be proposed. The key tool for the reuse of modernist buildings though remains the building itself, and its related narratives.